El impacto de la ventanilla única para el registro formal de empresas en República Dominicana - Vida Bobic; Lucía Delgado; María Paula Gerardino; Michael Hennessey; José Martinez-Carrasco (Inter-American Development Bank (IDB), 2023)
– Digital one-stop shops for firm registration can significantly reduce costs and increase access to information for firms entering the formal sector. This paper examines the impact of a nationwide program with a one-stop registration shop and lower registration fees. In addition to analyzing its impact on the number of firms registering in the formal sector, this study explores how the program reshapes the labor market for women and men. The empirical setting, the Dominican Republic, is characterized by high levels of firm and labor informality. The government launched the digital one-stop shop called Formalízate in 2013. To analyze its impact, this paper takes advantage of the sequential rollout of the program across provinces in the country. Results show that the launch of the program in a province is associated with a greater number of micro firms entering the formal market. Interestingly, these firms are concentrated in sectors in which informality was high prior to rollout of the program, especially the commerce and tourism sector. In addition, the results show that women's participation in the labor forced is impacted by the program, but men's participation is not. More specifically, the presence of Formalízate increased women's participation in the labor market as self-employed entrepreneurs.
Keywords: O17; O12; J40; 330; formalización; regulación de registro; evaluación de impacto; microempresas; autoempleo